Predialysis nephrology care and dialysis-related health outcomes among older adults initiating dialysis. Issue 1 (December 2016) - Fischer, Michael; Stroupe, Kevin; Kaufman, James; O'Hare, Ann; Browning, Margaret; Sohn, Min-Woong; Huo, Zhiping; Hynes, Denise
Abstract Background Predialysis nephrology care is associated with lower mortality and rates of hospitalization following chronic dialysis initiation. Whether more frequent predialysis nephrology care is associated with other favorable outcomes for older adults is not known. Methods Retrospective cohort study of patients ≥66 years who initiated chronic dialysis in 2000–2001 and were eligible for VA and/or Medicare-covered services. Nephrology visits in VA and/or Medicare during the 12-month predialysis period were identified and classified by low intensity (<3 visits), moderate intensity (3–6 visits), and high intensity (>6 visits). Outcome measures included very low estimated glomerular filtration rate, severe anemia, use of peritoneal dialysis, and receipt of permanent vascular access at dialysis initiation and death and kidney transplantation within two years of initiation. Generalized linear models with propensity score weighting were used to examine the association between nephrology care and outcomes. Results Among 58, 014 patients, 46 % had none, 22 % had low, 13 % had moderate, and 19 % had high intensity predialysis nephrology care. Patients with a greater intensity of predialysis nephrology care had more favorable outcomes (allp < 0.001). In adjusted models, patients with high intensity predialysis nephrology care were less likely to have severe anemia (RR = 0.70, 99 % CI: 0.65–0.74) and more likely to have permanent vascular access (RR = 3.60, 99 % CI: 3.42–3.79) at dialysis initiation, and less likely to die within two years of dialysis initiation (RR = 0.80, 99 % CI: 0.77–0.82). Conclusion In a large cohort of older adults treated with chronic dialysis, greater intensity of predialysis nephrology care was associated with more favorable outcomes.